PENGARUH SIKAP DAN PERSEPSI KONTROL PERILAKU TERHADAP NIAT WHISTLEBLOWING DENGAN PERSEPSI DUKUNGAN ORGANISASI SEBAGAI VARIABEL MODERASI - Novita Sari; Fransiska junita (JURNAL FAIRNESS, 2023)
Whistleblowing is an act of reporting fraud or violations committed by internal or external parties within an organization, Whistleblowing has an important role in disclosing fraud. This study aims to examine employee attitudes and perceptions of behavior control that affect whistleblowing intentions and perceptions of organizational support can be a moderating variable for attitudes and perceptions of behavior control. The sample in this study were employees of the Bengkulu City Tax Service Office. The data used in this study are primary data. The data collection method used purposive sampling technique and this study used a quantitative. Data were analyzed using multiple linear regression using SPSS software. The results showed that attitudes has effect on employee intentions and perceptions of behavior control has no effect on employee intentions in whistleblowing. Organizational support not have a moderating effect on attitudes, but has a moderating effect on perceptions of behavioral control on whistleblowing intentions.